Analysis of alu chip and realizing with pass transistor logic - U Win Lwin (2008)
This report describes the analysis of 74HC181 ALU CMOS IC chip and realising it with alternative CMOS logic circuit structure, called the pass transistor logic structure. The structure of internal circuits of ALU chip according to their logical functions and the circuits of the individual cell were explored up to the each MOS transistor's size. The measured MOS transistors' sizes were scaled down before simulation.